2004
DOI: 10.1111/j.1341-8076.2004.00153.x
|View full text |Cite
|
Sign up to set email alerts
|

Schönlein–Henoch purpura during pregnancy: Case report and review of the literature

Abstract: The clinical features of Schönlein-Henoch Purpura (SHP) consist of non-thrombocytopenic purpura in association with joint, gastrointestinal and renal involvements. Because it is uncommon in adults, there is little information on the effects of SHP on pregnancy in the literature. This report documents the clinical findings and outcome of an uncommon case of SHP affecting a woman who was 25 weeks pregnant. Prompt steroid-therapy induced a rapidly favorable course and successful vaginal delivery at 40 weeks gesta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 9 publications
(9 reference statements)
1
12
0
Order By: Relevance
“…According to studies the obstetrical outcome is found to be favourable in the absence of renal involvement 15,[21][22] this was seen in our case too where the kidneys remained unaffected. The risk of IgA vasculitis in the foetus was reported negligible as this immunoglobulin cannot cross the placenta.…”
Section: Chakrabarti Sb Et Al Int J Reprod Contracept Obstet Gynecolsupporting
confidence: 50%
“…According to studies the obstetrical outcome is found to be favourable in the absence of renal involvement 15,[21][22] this was seen in our case too where the kidneys remained unaffected. The risk of IgA vasculitis in the foetus was reported negligible as this immunoglobulin cannot cross the placenta.…”
Section: Chakrabarti Sb Et Al Int J Reprod Contracept Obstet Gynecolsupporting
confidence: 50%
“…In the whole literature, only 16 cases of HSP have been reported (14 in English, one in Japanese and one in Spanish) (Barquero-Romero et al 2006;Koizumi et al 2004;Cummins et al 2003;Ekoukou et al 1997;Le Goff et al 1997;Yasukawa et al 1996;Muszytowski and Ruszkiewicz-Folda 1996;Merill and Lahita 1994;Miyata et al 1994;Itoh et al 1994;Wilks et al 1993;Joseph et al 1987;Siroty 1985;Ray and Posen 1985;McCoy 1981;Plauche 1980). Therefore, this case is the 17th case reported worldwide in the literature.…”
Section: Discussionmentioning
confidence: 94%
“…Eleven women (Barquero-Romero et al 2006;Koizumi et al 2004;Cummins et al 2003;Ekoukou et al 1997;Le Goff et al 1997;Yasukawa et al 1996;Muszytowski and Ruszkiewicz-Folda 1996;Itoh et al 1994;Wilks et al 1993;Siroty 1985;McCoy 1981) revealed the disease during pregnancy and finally one of them postpartum (Miyata et al 1994). Renal involvement is more frequent and severe in adults than in childhood (Blanco et al 1997), but it usually has an excellent outcome.…”
Section: Discussionmentioning
confidence: 95%
“…[13][14][15][16][17] There are numerous case reports in the literature of patients with truncal rash and concomitant renal involvement. [18][19][20][21][22][23][24][25][26][27][28] In a retrospective study of 57 adult cases of biopsy-confirmed HSP, Tancrede-Bohin et al [15] were able to show a significant association between IgA glomerulonephritis and the spread of purpura to areas above the waist. Hung et al [17] have shown that purpura extends above the umbilicus more commonly in children with a urinalysis abnormality lasting >1 year as compared with children in whom urinalysis abnormalities resolved within 1 year, suggesting increased renal involvement when truncal purpura is present.…”
Section: Discussionmentioning
confidence: 99%
“…These gastrointestinal cases include both adults and children, cutaneous manifestations both preceding and following gastrointestinal symptoms, lesions ranging from scant petechiae to diffuse purpura, and outcomes ranging from spontaneous resolution of abdominal colic to intestinal hemorrhage and death. [20,27,[29][30][31][32][33][34][35][36][37][38][39][40][41] While it is uncommon for nephritis to precede the onset of cutaneous purpura, abdominal pain has been shown to precede skin involvement by up to 2 weeks in 19% of children with HSP. [17] Regardless, cutaneous manifestations precede gastrointestinal involvement in the majority of cases.…”
Section: Discussionmentioning
confidence: 99%